(untitled) (Journal of Educational Sciences, 2016)
В статье рассматривается экспериментальные работы по детским телепередачам. Автор на основе детских передач представляет вопросы и итоги экпериментальных работпо эстетическому воспитанию младших школьников. In article is considered experimental works on children’s telecasts. The author on the basis of children’s transfers represents questions and results of experimental works on esthetic education of elementary school.